Implementasi Algoritma Support Vector Machine dan Model Bag-of-Words dalam Analisis Sentimen mengenai PILKADA 2020 pada Pengguna Twitter - Raja Farhan Ramadha Pohan; Dian Eka Ratnawati; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Social media is a digital platform used to gather information. One of the social media in Indonesia that has the most users is Twitter. Twitter is a social media platform in a form of a microblog, that allows users to exchange opinions and share ideas. One of the topics that was widely discussed on Twitter was the implementation of the Pilkada 2020. Pilkada 2020 attracted the attention of many Twitter users because the implementation was carried out in the midst of a pandemic. Tweets or tweets of Twitter users here are used as objects to conduct sentiment analysis on related topics. This analysis process is carried out by implementing the Support Vector Machine algorithm to classify positive and negative tweets. This study uses 400 tweets, consisting of 187 positive tweets and 213 negative tweets. The scores of accuracy, precision, recall, and f1-score in this machine learning model are 87.5%, 87.4%, 87.4%, and 87.4%, respectively. This value is obtained using the C parameter of 5, and the max_iter parameter of 100.